ADMINISTRATIVE SYSTEM OF GOODS ON DELIVERY PT.RAHMAT 6.0 USING MICROSOFT VISUAL BASIC - Yudhi Renur; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2008)
The development of increasingly sophisticated computer that is very helpful in dataprocessing still using manual systems. This is often meninbulkan issues related to theaccuracy of the data which resulted in delays in data processing. Valuableinformation is the information quickly and accurately. Then needed a computerizedsystem as a supporter. Service delivery system is designed with the aim to simplifythe processing of data and preparing reports.